2021
DOI: 10.3390/molecules27010256
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Bacterial Recognition over a Wide pH Range by Boronic Acid-Based Ditopic Dendrimer Probes for Gram-Positive Bacteria

Abstract: We have developed a convenient and selective method for the detection of Gram-positive bacteria using a ditopic poly(amidoamine) (PAMAM) dendrimer probe. The dendrimer that was modified with dipicolylamine (dpa) and phenylboronic acid groups showed selectivity toward Staphylococcus aureus. The ditopic dendrimer system had higher sensitivity and better pH tolerance than the monotopic PAMAM dendrimer probe. We also investigated the mechanisms of various ditopic PAMAM dendrimer probes and found that the selectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…Previous studies have shown that S. aureus grows at pH 4.0− 9.8 28 and E. coli thrives at pH 4.5−9.0. 29 Figure 2A shows that whereas B-PAMAM(+), which is based on the PAMAM(G4) dendrimer, selectively recognized Gram-positive bacteria (including S. aureus IAM1011), producing aggregates and decreasing turbidity, 21,23 B-PAMAM(−), which is based on the PAMAM(G3.5) dendrimer, did not cause any changes in both E. coli K12W3110 and S. aureus IAM1011 suspensions. The results indicate that negatively charged dendrimer probes fail to recognize bacteria because of the repulsive force produced between the probes and bacteria having a negatively charged surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that S. aureus grows at pH 4.0− 9.8 28 and E. coli thrives at pH 4.5−9.0. 29 Figure 2A shows that whereas B-PAMAM(+), which is based on the PAMAM(G4) dendrimer, selectively recognized Gram-positive bacteria (including S. aureus IAM1011), producing aggregates and decreasing turbidity, 21,23 B-PAMAM(−), which is based on the PAMAM(G3.5) dendrimer, did not cause any changes in both E. coli K12W3110 and S. aureus IAM1011 suspensions. The results indicate that negatively charged dendrimer probes fail to recognize bacteria because of the repulsive force produced between the probes and bacteria having a negatively charged surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…35 We had previously reported that boronic acid has the potential to form bonds with the cis-diols of saccharides on the surface of both Gram-positive and Gram-negative bacteria. 23 We considered that the binding force of boronic acid groups was stronger for Gram-positive bacteria than for Gramnegative bacteria. However, as indicated in Figures 2 and 3, boronic acid itself could not recognize bacteria, and the presence of electrostatic interaction was crucial for the recognition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations